Non-Performing Loan Settlement by Fintech Lending in Unsecured Credit Sale and Purchase Transactions: To Do or Not to Do - Anggraeny, Isdian; Ayu, Isdiyana Kusuma; Rahmah, Sintia; Nur, Asrul Ibrahim; Wulandari, Siti (Indonesia Law Reform Journal, 2023)
PT Shopee International Indonesia is a company that focuses on digital applications, especially e-commerce, and is one of the largest online marketplaces in Indonesia. This online shopping system offers the latest innovations in credit-based payment methods without collateral, such as pay later, along with the advancement of the digital world. This research seeks to find out the procedures for implementing transactions, resolving non-performing loans, and legal protection provided to Fintech Lending (financial technology) organizers in Shopee Pay-Later. This includes identifying the rights and obligations of the parties involved, as well as the legal consequences of the Shopee Pay-later credit financing agreement. The research uses an empirical legal research method, which uses a problem-solving approach to data collected from observations and study findings. The research findings show that in order to finance a Shopee Pay-later unsecured credit agreement, buyers must electronically sign an agreement confirming that they accept its terms. The parties are obligated by the terms of the agreement, under which they must not contravene the relevant laws and regulations and must fulfil their rights and obligations according to the financing agreement. The district court or arbitration can be used to sue either party if they commit a default, as specified in Article 1243 of the Civil Code, or violate the law, as specified in Article 1365 of the Civil Code.   Abstrak Shopee International Indonesia adalah perusahaan yang fokus pada aplikasi digital, terutama e-commerce, dan merupakan salah satu pasar online terbesar di Indonesia. Sistem belanja online ini menawarkan inovasi terbaru dalam metode pembayaran berbasis kredit tanpa agunan, seperti bayar di belakangan, seiring dengan kemajuan dunia digital. Tujuan dari penelitian ini adalah untuk mengetahui tata cara pelaksanaan transaksi, penyelesaian kredit macet, dan perlindungan hukum yang diberikan kepada penyelenggara Fintech Lending (financial technology) di Shopee Pay-later. Hal ini termasuk mengidentifikasi hak dan kewajiban para pihak yang terlibat, serta akibat hukum dari adanya perjanjian pembiayaan kredit Shopee Pay-later. Penelitian menggunakan metode penelitian hukum empiris, yaitu dengan menggunakan pendekatan pemecahan masalah terhadap data yang dikumpulkan melalui pengamatan dan temuan studi. Temuan penelitian menunjukkan bahwa untuk membiayai perjanjian kredit tanpa jaminan Shopee Pay-later, pembeli harus menandatangani perjanjian secara elektronik yang mengonfirmasi bahwa mereka menerima persyaratannya. Para pihak diwajibkan oleh ketentuan perjanjian, yang berarti mereka tidak boleh bertentangan dengan hukum dan peraturan yang relevan dan harus memenuhi hak dan kewajiban mereka sesuai dengan perjanjian pembiayaan. Pengadilan negeri atau arbitrase dapat digunakan untuk menuntut salah satu pihak jika mereka melakukan wanprestasi, seperti yang ditentukan dalam Pasal 1243 KUH Perdata, atau melanggar hukum, seperti yang ditentukan dalam Pasal 1365 KUH Perdata.